A nickel-based superalloy for additive manufacturing and a method of making the same
Patent Information
- Application Number
- CN202611154420.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,增材制造过程存在快速加热、快速冷却的固有特征,虽有助于细化合金晶粒、提升组织均匀性,但也带来了一系列技术难题:制备过程中易在合金内部形成微孔、微裂纹等缺陷,且快速的温度变化导致合金中强化相来不及充分析出,直接影响合金的成型质量与力学性能;为适配增材制造工艺,现有技术多通过成分调整或后处理工艺优化改善合金成型性,如增加C、Hf元素含量降低裂纹敏感性,却引发合金组织稳定性下降的问题,或降低B、Zr元素含量减少裂纹密度,但无法实现裂纹的完全消除;同时,单独依靠热等静压、热处理等工艺优化调整合金微观组织,仍难以弥补成分设计的先天不足,无法使增材制造镍基高温合金的综合性能达到传统铸造合金的指标要求
(1)本发明通过精准的合金成分设计,优化了合金的增材制造成型性,从根源上降低裂纹敏感性,同时为多级γ′相和碳化物的析出提供成分基础;通过优化的粉末制备工艺,获得球形度高、杂质少、粒径适配的合金粉末,为增材制造的成型质量奠定原料基础;再结合适配的SLM增材制造工艺及后处理工艺,实现合金缺陷消除与组织强化的协同,最终制得的镍基高温合金致密度高、内部无裂纹,且具备多级γ′相强化的微观组织,室温及高温力学性能优异。
Smart Images

Figure CN122879557A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing 3D printing technology, specifically relating to a nickel-based high-temperature alloy for additive manufacturing and its preparation method. Background Technology
[0002] High-temperature alloys, due to their excellent high-temperature resistance, oxidation resistance, fatigue resistance, and corrosion resistance, have become key materials for core components of high-end equipment such as aerospace. Traditional manufacturing technologies, including investment casting, powder metallurgy, and deformation processing, can achieve large-scale production of high-temperature alloys, but they have significant limitations when manufacturing complex structural components. Not only are mold design and processing cycles long, but material utilization is low, and production costs remain high. Furthermore, they are difficult to meet the design requirements of high-end equipment for complex component configurations and integrated molding. As the demand for high-temperature, high-strength materials and complex precision components in the aerospace field continues to grow, the shortcomings of traditional manufacturing technologies are becoming increasingly prominent.
[0003] Additive manufacturing (AM) technology, especially selective laser melting (SLM), offers a novel solution for the fabrication of complex high-temperature alloy components due to its advantages of moldless forming and integrated design and manufacturing. It can directly form complex and intricate structures, significantly shortening production cycles and improving material utilization. Furthermore, it allows for the optimization of material microstructure and properties through precise control of the manufacturing process. Currently, this technology is becoming increasingly mature in the fabrication of materials such as stainless steel and titanium alloys. Nickel-based superalloys, especially those with high γ' phase content, have become a research hotspot in the field of additive manufacturing due to their superior high-temperature mechanical properties, and related technology development is actively underway.
[0004] However, additive manufacturing inherently involves rapid heating and cooling, which, while helping to refine alloy grains and improve microstructure uniformity, also presents a series of technical challenges: defects such as micropores and microcracks easily form within the alloy during preparation, and rapid temperature changes prevent the strengthening phases from fully dispersing, directly affecting the alloy's forming quality and mechanical properties. To adapt to additive manufacturing, existing technologies often improve alloy formability through composition adjustments or post-processing optimizations, such as increasing C and Hf content to reduce crack sensitivity, but this leads to decreased alloy microstructure stability; or reducing B and Zr content to decrease crack density, but cannot completely eliminate cracks. Furthermore, relying solely on hot isostatic pressing and heat treatment to optimize the alloy's microstructure is insufficient to compensate for inherent deficiencies in composition design, making it impossible for additively manufactured nickel-based superalloys to meet the performance requirements of traditional cast alloys.
[0005] In summary, existing nickel-based superalloys for additive manufacturing still suffer from technical challenges such as easy cracking, insufficient precipitation of reinforcing phases, poor microstructural stability, and substandard overall performance. Simple process optimization or single-component adjustments cannot fundamentally solve these problems. Therefore, there is an urgent need to develop a nickel-based superalloy adapted to the characteristics of additive manufacturing processes. Through precise composition development, optimized powder raw material preparation processes, and synergistic control of process and composition, the cracking problem in additive manufacturing can be fundamentally solved, achieving reasonable precipitation of reinforcing phases and microstructural stability, improving the overall mechanical properties of the alloy, and meeting the performance requirements of aerospace and other fields for complex additive-manufactured superalloy components. Summary of the Invention
[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0007] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0008] This invention discloses an additive manufacturing method for nickel-based superalloys and its preparation method, belonging to the field of nickel-based superalloy preparation technology. It aims to solve the technical problems of existing additive manufacturing nickel-based superalloys, such as easy cracking, insufficient precipitation of strengthening phases, poor microstructure stability, and substandard comprehensive performance. Through precise composition design, optimized powder preparation process, and synergistic control of appropriate additive manufacturing and post-processing processes, the alloy's formability and mechanical properties are improved, meeting the additive manufacturing needs of complex high-temperature alloy components in aerospace and other fields.
[0009] (a) Composition design of nickel-based superalloys for additive manufacturing This invention provides an additive manufacturing method for a γ′ phase-strengthened nickel-based superalloy. The strengthening phase in the microstructure of the nickel-based superalloy includes a multi-level γ′ phase and carbides. Specifically, the multi-level γ′ phase consists of a first γ′ phase, a second γ′ phase, and a third γ′ phase. The synergistic precipitation of the multi-level γ′ phase can achieve efficient strengthening of the alloy, while the carbides further enhance the grain boundary strength and microstructure stability of the alloy. The density of the additively manufactured nickel-based superalloy is not less than 99.0%, preferably ≥99.9%; more preferably, the additively manufactured nickel-based superalloy has no internal cracks and excellent forming quality.
[0010] The chemical composition of the additively manufactured γ′ phase strengthened nickel-based superalloy, by weight percentage, includes: Co: 8.0-10.0 wt.%, Cr: 15.0-17.0 wt.%, Al: 3.2-4.0 wt.%, Ti: 3.2-3.7 wt.%, Ta: 1.5-3.0 wt.%, W: 2.0-4.0 wt.%, Mo: 1.5-3.0 wt.%, Nb: 0.5-2.0 wt.%, C: 0-0.2 wt.%, Zr: 0-0.15 wt.%, B: 0-0.02 wt.%, Sc: 0-1.0 wt.%, with the balance being Ni; Preferably, the chemical composition, by weight percentage, includes: Co: 8.0-9.0 wt.%, Cr: 15.0-16.0 wt.%, Al: 3.5-3.7 wt.%, Ti: 3.4-3.6 wt.%, Ta: 1.5-3.0 wt.%, W: 2.0-3.0 wt.%, Mo: 1.5-2.0 wt.%, Nb: 0.5-2.0 wt.%, C: 0.1-0.15 wt.%, Zr: 0.05-0.10 wt.%, B: 0.005-0.015 wt.%, Sc: 0-1.0 wt.%, with the balance being Ni.
[0011] Preferably, the additively manufactured γ′ phase strengthened nickel-based superalloy possesses excellent room temperature and high temperature mechanical properties, with the following specific characteristics: (i) In the printed state, the room temperature tensile strength exceeds 1200 MPa, and the room temperature elongation at break exceeds 20%; (ii) After aging treatment, the room temperature tensile strength exceeds 1380 MPa, and the room temperature elongation at break exceeds 25%; (iii) After aging treatment, the tensile strength at 650℃ exceeds 1200MPa and the elongation at break at 650℃ exceeds 20%.
[0012] The design and preparation method of the aforementioned high-performance nickel-based alloy includes the following steps: Using Co, Cr, Mo, W, Al, Ti, Nb, Ta, C, B, Zr, and Ni as the components of the nickel-based alloy, thermodynamic calculations were performed on the main elements affecting alloy cracking and the amount of harmful phase precipitation to establish the relationship between composition, solidification path, and cracking tendency. Ultimately, the optimal range of nickel-based alloy composition was obtained by using the reduction of alloy cracking tendency and the avoidance of harmful phase precipitation as the design criteria. Simultaneously, the effects of different trace elements C, B, and Zr on alloy viscosity were studied, and the cracking tendency during forming was reduced by optimizing the spread of the molten pool during additive manufacturing. Through the precise proportioning of the above components, the crack sensitivity during alloy additive manufacturing is reduced while ensuring sufficient precipitation of the γ′ phase and reasonable formation of carbides, thus balancing the alloy's formability and high-temperature mechanical properties. In the alloy of this invention, the innovative addition of Sc element achieves a synergistic breakthrough in the room-temperature and high-temperature mechanical properties of the heat-treated sample while maintaining alloy formability, demonstrating a certain degree of creativity.
[0013] (II) Preparation method of nickel-based superalloy powder for additive manufacturing This invention also provides a powder preparation method for the above-mentioned additive manufacturing nickel-based superalloy, comprising the following steps: Powder formulation design: According to the mass fraction of the chemical composition of the above nickel-based superalloy, accurately weigh the component elements or intermediate alloy, and mix them thoroughly to prepare a mixture; Tool purification: Coat all stirring tools with titanium dioxide to prevent impurities from being introduced during stirring and affecting alloy purity; dry crucibles and other smelting tools to ensure the dryness of the powder-making environment and prevent moisture from being introduced. Vacuum melting: The above mixture is placed in an induction melting furnace for vacuum melting. The vacuum melting temperature is 1000~1600℃, the gas pressure inside the melting furnace is 2.2~3.5MPa, and the vacuum degree is 20~70Pa. Atomization powder production: Argon gas is used as the atomization medium to atomize the molten alloy into powder. The argon gas has a purity of 99.99% and an atomization pressure of 2~6MPa. Drying and sieving: The alloy powder obtained by atomization is sieved. The average particle size of the alloy powder after sieving is 15~53μm. Then, the sieved powder is vacuum dried and sealed for later use. Preferably, the vacuum melting process involves a melting temperature of 1450~1600℃, a gas pressure of 2.2~3.5MPa inside the melting furnace, and a vacuum degree of 20~70Pa. Preferably, the atomization powdering is carried out under an argon atmosphere, the purity of the argon is 99.99%, and the atomization pressure is 3.5~4.5MPa; The nickel-based superalloy powder prepared by the above method has excellent sphericity, a very low proportion of satellite powder and irregular powder, and good powder flow properties. It can be directly adapted to the powder spreading and feeding requirements of additive manufacturing processes, and effectively avoids defects such as micropores and incomplete fusion caused by powder quality problems in additive manufacturing processes.
[0014] (III) Process parameters for additive manufacturing of nickel-based superalloys This invention further provides a method for preparing the above-mentioned additive manufacturing γ′ phase strengthened nickel-based superalloy, comprising the following steps: ① Additive manufacturing process: Selective laser cladding (SLM) additive manufacturing process is adopted, using the nickel-based superalloy powder prepared above as raw material to obtain a printed nickel-based superalloy; wherein, the SLM process parameters are: laser power 150-250W, scanning rate 600-1100mm / s, layer rotation angle 90°, single layer thickness 0.03-0.05mm, track spacing 0.06-0.10mm, laser spot diameter 0.05-0.08mm; Ar gas is preferably used as protective gas.
[0015] ② Heat treatment: Based on the structural characteristics of the additively manufactured printed parts, hot isostatic pressing (HIP) is performed on the printed parts to eliminate internal pores and cracks, and improve the material density and mechanical properties. The melting temperature of the γ′ phase and the transformation temperature of the precipitated phase of the nickel-based superalloy are determined by testing, and the process parameter range of HIP is defined accordingly to avoid the melting of the γ′ phase during the process. At the same time, suitable solution treatment and aging treatment process parameters are designed to ensure that the multi-level γ′ phase of the above three sizes is formed in the microstructure of the alloy after aging treatment.
[0016] In the hot isostatic pressing (HIP) step, the printed nickel-based superalloy is subjected to HIP treatment. The specific process is as follows: the temperature is raised to 1200°C at a heating rate of 10°C / min, and held at 1200°C and 180MPa for 2 hours. Then, the temperature is lowered by furnace cooling to obtain the printed part after HIP treatment. This process can effectively eliminate internal micropores and microcracks caused by additive manufacturing and significantly improve the density of the alloy.
[0017] In the solution and aging treatment steps: the printed part after hot isostatic pressing is subjected to a two-step heat treatment of solution and aging: first, the temperature is raised to 1160℃ at a heating rate of 5℃ / min for 2 hours for solution treatment, and then cooled by air cooling to obtain the solution-treated sample; then the solution-treated sample is raised to 800℃ at a heating rate of 5℃ / min for 24 hours for aging treatment, and then cooled by air cooling to finally obtain the additively manufactured γ′ phase strengthened nickel-based superalloy.
[0018] The above preparation method can achieve precise control of the alloy microstructure, which can eliminate the inherent defects in the additive manufacturing process and promote the uniform precipitation of multi-level γ′ phase and carbides. Finally, additive-manufactured nickel-based superalloys with high density, no cracks, and excellent mechanical properties at room temperature and high temperature can be obtained. Its performance can reach or even exceed that of traditional cast nickel-based superalloys, which fully meets the requirements of high-end fields such as aerospace for the use of complex high-temperature alloy components.
[0019] Beneficial effects of this invention: (1) This invention optimizes the additive manufacturing formability of the alloy through precise alloy composition design, reduces crack sensitivity from the source, and provides a compositional basis for the precipitation of multi-level γ′ phase and carbides. Through optimized powder preparation process, alloy powder with high sphericity, few impurities and suitable particle size is obtained, laying the raw material foundation for the forming quality of additive manufacturing. Combined with suitable SLM additive manufacturing process and post-processing process, the alloy defect elimination and microstructure strengthening are synergistically achieved. The resulting nickel-based high temperature alloy has high density, no internal cracks and has a microstructure strengthened by multi-level γ′ phase, with excellent room temperature and high temperature mechanical properties.
[0020] (2) The alloy and preparation method of the present invention are adapted to the rapid heating and rapid cooling process characteristics of additive manufacturing, which solves the technical problems of easy cracking, insufficient precipitation of strengthening phase and substandard performance of nickel-based high-temperature alloys in existing additive manufacturing. It realizes high-quality additive manufacturing of complex high-temperature alloy components, while shortening the production cycle and reducing manufacturing costs. It provides a new solution for the preparation of complex high-temperature alloy components in aerospace and other fields, and has good industrial application prospects.
[0021] (3) The alloy designed in this invention has excellent room temperature and high temperature mechanical properties under heat treatment. The ductility of nickel-based high temperature alloys is improved by introducing only a low mass fraction of Sc element. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 The image shows a scanning electron microscope image of nickel-based superalloy powder under the gas atomization process parameters of Embodiment 1 of the present invention. Figure 2 This is a scanning electron microscope image of an additively manufactured nickel-based superalloy in the printed state according to Embodiment 1 of the present invention; Figure 3 This is a macroscopic view of the nickel-based superalloy after complete heat treatment according to Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the additively manufactured nickel-based superalloy prepared in Example 1 of the present invention after complete heat treatment; Figure 5 This is a microstructure diagram of the printed part prepared from the powder of Comparative Example 5 of this invention; Figure 6 This is a microstructure diagram of the printed part prepared from the powder of Comparative Example 6 of this invention; Figure 7 This is a microstructure diagram of the printed part prepared from the powder of Comparative Example 7 of this invention; Figure 8 This is a microstructure diagram of the printed part prepared from the 12-component powder of Comparative Example 1 of this invention; Figure 9 This is a graph showing the viscosity calculation data of the components in Comparative Example 12 and Example 1 of the present invention; Figure 10 This is a diagram showing the bag blockage situation of powder raw material preparation under the gas atomization process parameters of Comparative Example 13 of the present invention; Figure 11 The image shown is a scanning electron microscope image of nickel-based superalloy powder under the gas atomization process parameters of Comparative Example 14 of this invention. Figure 12 The image shown is a scanning electron microscope image of nickel-based superalloy powder under the gas atomization process parameters of Comparative Example 15 of this invention. Figure 13 This is a microstructure diagram of the printed part prepared from the powder of Comparative Example 16 of this invention. Detailed Implementation
[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0024] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0026] Unless otherwise specified, all raw materials used in the embodiments of this invention are commercially available.
[0027] Example 1 (1) In this embodiment, an additive manufacturing nickel-based superalloy is prepared. The additive manufacturing nickel-based superalloy comprises the following chemical composition by weight percentage: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.15 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 1.0 wt.%, balance Ni.
[0028] (2) Powder raw material preparation: All raw materials are mixed and nickel-based high-temperature alloy powder is prepared by argon atomization system. The crucible is a zirconium oxide crucible, the melting power is 65kW, the continuous holding time is 25min, the melting temperature is 1500℃, and the atomization pressure is 4MPa. The nickel-based alloy powder with a particle size of 15~53μm is screened out by vibrating sieving equipment for laser additive manufacturing.
[0029] (3) Additive manufacturing process: The layer thickness was controlled at 30 μm, the scanning spacing at 80 μm, the laser power at 200 W, the laser spot diameter at 80 μm, the scanning rate at 900 mm / s, and the interlayer rotation angle at 90°. An orthogonal scanning strategy was adopted, and argon was used as the protective gas. The formed sample was a rectangular prism specimen with dimensions of 20 mm × 20 mm × 70 mm. Subsequently, the additively manufactured nickel-based superalloy specimen was subjected to heat treatment and performance testing according to the following steps: (4) Hot Isostatic Pressing (HIP): The printed parts are subjected to HIP to obtain HIP-treated printed parts. The parameters of HIP are as follows: the HIP temperature is 1200℃ and the HIP pressure is 180MPa; the printed parts are kept at the HIP temperature and pressure for 2 hours and then cooled in the furnace to obtain HIP-treated printed parts; the heating rate of the printed parts to the HIP temperature is 10℃ / min.
[0030] (5) Solution treatment: The printed part after hot isostatic pressing is subjected to solution treatment to obtain a solution-treated printed part. Specifically, the printed part after hot isostatic pressing is heated to 1160°C and subjected to solution treatment for 2 hours, and then removed and air-cooled to room temperature to obtain a solution-treated printed part; wherein the heating rate is 5°C / min.
[0031] (6) Aging treatment: The solution-treated printed part is subjected to aging treatment to obtain an additively manufactured nickel-based superalloy. The solution-treated printed part is heated to 800°C and aged for 24 hours, then removed and air-cooled to room temperature to obtain the aged printed part; wherein the heating rate is 5°C / min.
[0032] (7) The additive manufacturing nickel-based high-temperature alloy sample after heat treatment is sliced and sent to a scanning electron microscope for observation. The microstructure reaches the expected effect, and the heat treatment is over.
[0033] (8) The additively manufactured nickel-based superalloy sample after complete heat treatment is processed into a tensile sample and mechanical property test is completed.
[0034] Figure 1 The image shown is a scanning electron microscope image of nickel-based superalloy powder under the gas atomization process parameters in Example 1. It can be seen that the powder has good sphericity, almost no satellite powder, and the powder particle size distribution meets the raw material requirements of the selective laser melting additive manufacturing process.
[0035] Figure 2 Scanning electron microscope images of the additively manufactured nickel-based superalloy in the printed state show that there are almost no unfused pores and no microcracks in the matrix of the printed alloy.
[0036] Figure 3 The image shows the macroscopic appearance of the nickel-based superalloy after complete heat treatment in this embodiment. It can be seen that the sample surface is dense and there is no obvious oxidation or peeling. The sample did not crack after being treated with the heat treatment regime of this embodiment.
[0037] Figure 4 The images shown are scanning electron microscope images of the additively manufactured nickel-based superalloy prepared in this embodiment after complete heat treatment, for comparison. Figure 2 It can be seen that, compared to the printed state, the alloy achieved full densification after complete heat treatment, with porosity and microcracks completely disappearing. In addition, a high volume fraction of γ' phase with spherical shape and uniform size precipitated in the fully heat-treated microstructure. At a lower aging temperature, the precipitation of carbides and borides was suppressed to a certain extent, ensuring the high-temperature mechanical properties of the alloy.
[0038] The instantaneous tensile properties of the additively manufactured nickel-based superalloy in the printed and heat-treated states prepared in this embodiment are shown in Table 1. The raw material input and powder output data for powder preparation in this embodiment are shown in Table 2.
[0039] It should be noted that the additive manufacturing nickel-based superalloy designed in this invention is suitable for powder bed melting process, and the required particle size of the powder raw material is 15~53μm. Therefore, the 15~53μm powder yield ratio is used as the screening standard for the process parameters of the powder raw material preparation process.
[0040] Table 1
[0041] Table 2
[0042] Comparative Example 1 The difference from Example 1 is in step (1): Compared to Example 1, no trace elements, including carbon (C), zirconium (Zr) and boron (B), were added in Comparative Example 1, and 1 wt.% of scandium (Sc) was not introduced. The contents of other elements were the same, and the specific composition is as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt. %, Mo: 1.5wt.%, Nb: 2.0wt.%, C: 0wt.%, Zr: 0wt.%, B: 0wt.%, Sc: 0wt.%, the balance is Ni.
[0043] Comparative Example 2 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 2 did not add carbon and boron, two trace elements; the zirconium content was different; and 1 wt.% of scandium was not introduced. The contents of other elements were the same. The specific composition is as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt.% , Mo: 1.5wt.%, Nb: 2.0wt.%, C: 0wt.%, Zr: 0.05wt.%, B: 0wt.%, Sc: 0wt.%, the balance is Ni.
[0044] Comparative Example 3 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 3 did not add carbon and boron, two trace elements, and did not introduce 1 wt.% scandium. The contents of other elements were the same, and the specific components are as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt.% , Mo: 1.5wt.%, Nb: 2.0wt.%, C: 0wt.%, Zr: 0.1wt.%, B: 0wt.%, Sc: 0wt.%, the balance is Ni.
[0045] Comparative Example 4 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 4 did not add carbon and boron, two trace elements; the zirconium content was different; and 1 wt.% of scandium was not introduced. The contents of other elements were the same. The specific composition is as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt.% , Mo: 1.5wt.%, Nb: 2.0wt.%, C: 0wt.%, Zr: 0.15wt.%, B: 0wt.%, Sc: 0wt.%, the balance is Ni.
[0046] Comparative Example 5 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 5 did not add carbon, had a different boron content, and did not introduce 1 wt.% scandium. The contents of other elements were the same. The specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0 wt.%, Zr: 0.1 wt.%, B: 0.005 wt.%, Sc: 0 wt.%, balance Ni.
[0047] Comparative Example 6 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 6 did not add carbon, did not introduce 1 wt.% scandium, and the contents of other elements were the same. The specific components are as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt.%, Mo: 1.5wt.%, Nb: 2.0wt.%, C: 0wt.%, Zr: 0.1wt.%, B: 0.01wt.%, Sc: 0wt.%, and the balance is Ni.
[0048] Microstructure diagram of the printed part prepared from the powder of Comparative Example 6, see [link / reference]. Figure 6 As shown. From Figure 6 It can be seen that a small number of cracks appeared inside the sample prepared by the components in Comparative Example 6, indicating a high sensitivity to cracks.
[0049] This shows that adding a small amount of carbon can reduce the susceptibility to cracking during alloy additive manufacturing and increase the weldability of the alloy.
[0050] The instantaneous tensile properties of the additively manufactured nickel-based superalloys prepared in this comparative example in the printed and heat-treated states are shown in Table 3.
[0051] Table 3
[0052] Comparative Example 7 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 7 did not add carbon, had a different boron content, and did not introduce 1 wt.% scandium. The contents of other elements were the same. The specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0 wt.%, Zr: 0.1 wt.%, B: 0.015 wt.%, Sc: 0 wt.%, balance Ni.
[0053] Comparative Example 8 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 8 has a different carbon content and does not introduce 1 wt.% scandium, while the contents of other elements are the same. The specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.05 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 0 wt.%, balance Ni.
[0054] Comparative Example 9 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 9 has a different carbon content and does not introduce 1 wt.% scandium, while the contents of other elements are the same. The specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.1 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 0 wt.%, balance Ni.
[0055] Comparative Example 10 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 10 did not add scandium, nor did it introduce 1 wt.% of scandium. The contents of other elements were the same, and the specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.15 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 0 wt.%, balance Ni.
[0056] The instantaneous tensile properties of the additively manufactured nickel-based superalloys prepared in this comparative example in both printed and heat-treated states are shown in Table 4.
[0057] Analysis of the comparative example 1 shows that the 1 wt.% scandium element innovatively introduced in this invention can significantly improve the room temperature and high temperature tensile properties of the sample after heat treatment. The elongation of the alloy at 25°C can be increased by nearly 76%, and the elongation of the alloy at 650°C can be increased by nearly 70%.
[0058] Table 4
[0059] Comparative Example 11 The difference from Example 1 is in step (1): Compared to Example 1, Comparative Example 11 has a different carbon content and does not introduce 1 wt.% scandium, while the contents of other elements are the same. The specific composition is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.2 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 0 wt.%, balance Ni.
[0060] Comparative Example 12 The difference from Example 1 is in step (1): compared to Example 1, Comparative Example 12 did not add trace element boron (B), while the contents of other elements were the same. That is, the chemical composition of the alloy in Comparative Example 12 is different from that in Example 1, but the others are the same.
[0061] The chemical composition of the additively manufactured nickel-based superalloy in Comparative Example 12 is as follows: Co: 9.0wt.%, Cr: 16.0wt.%, Al: 3.7wt.%, Ti: 3.5wt.%, Ta: 2.0wt.%, W: 2.5wt.%, M o: 1.5wt.%, Nb: 2.0wt.%, C: 0.15wt.%, Zr: 0.1wt.%, B: 0wt.%, Sc: 1.0wt.%, the balance is Ni.
[0062] Microstructure diagram of the printed part prepared from the 12-component powder in Comparative Example 12, see [link / reference]. Figure 8 As shown. From Figure 8 It can be seen that the sample prepared from the components in Comparative Example 12 has many cracks inside, indicating a high crack sensitivity.
[0063] Viscosity calculation data for the components of Comparative Example 12 and Example 1 can be found in [reference]. Figure 9 As shown, the viscosity of Comparative Example 12 (without element B) is lower than that of Example 1. This shows that adding a small amount of boron to an alloy can increase its viscosity, reduce the risk of cracking, and increase its weldability.
[0064] Table 5. Mass fraction percentage (wt.%) of each component in Example 1 and Comparative Examples 1-12
[0065] The components listed in Table 5 were formed using additive manufacturing. Specific forming parameters were as follows: layer thickness of 30 μm, scanning spacing of 80 μm, laser power of 200 W, laser spot diameter of 80 μm, scanning rate of 900 mm / s, interlayer rotation angle of 90°, orthogonal scanning strategy, and argon as the protective gas. The formed sample was a rectangular prism specimen with dimensions of 20 mm × 20 mm × 70 mm. The formed sample was cut using electrical discharge machining (EDM), and the forming quality was determined by analyzing the microstructure using an optical microscope. The forming quality was mainly assessed by observing whether internal cracks existed in the sample. The crack size and porosity results are shown in Table 6. Table 6
[0066] Analysis of the samples with different compositions shows that the addition of Zr can suppress crack initiation, especially cracks larger than 100µm. However, when the Zr content exceeds 0.1wt.% and reaches 0.15wt.%, the porosity of the sample increases. Therefore, a Zr content of 0.1wt.% is determined to be the optimal content. The addition of B can suppress porosity, but when the B content exceeds 0.01wt.% and reaches 0.015wt.%, the porosity of the sample increases dramatically, and the crack density also increases. A 100µm crack reappeared, thus determining that a B content of 0.01wt.% is the optimal content. The addition of C element can suppress crack formation, but when the C content exceeds 0.15wt.% and reaches 0.2wt.%, the plasticity of the sample will decrease. The room temperature tensile properties of Comparative Example 11 in the printed state were measured as follows: yield strength: 920MPa, tensile strength: 932MPa, elongation: 0.7%, which are much lower than the performance of Comparative Example 10. Therefore, a C content of 0.15wt.% is determined to be the optimal content.
[0067] Based on the optimal composition obtained from the trace element optimization section, the preparation process of powder raw materials used in additive manufacturing was studied, as described in Comparative Examples 13-15 below.
[0068] Comparative Example 13 The difference from Example 1 is that in step (2): the melting temperature of the powder preparation in Comparative Example 13 is different from that in Example 1, but the rest is the same.
[0069] Among them, Comparative Example 13 was prepared from powder raw materials: All raw materials were mixed and nickel-based superalloy powder was prepared by argon atomization system. The crucible was a zirconia crucible, the melting power was 60kW, the holding time was 15min, the melting temperature was 1350℃, and the atomization pressure was 4MPa. The nickel-based alloy powder with a particle size of 15~53μm was screened out by vibrating sieving equipment for laser additive manufacturing.
[0070] It should be noted that in the gas atomization powder preparation process, the temperature of the molten metal must reach the atomization requirement before the atomization process begins; otherwise, powder preparation will fail.
[0071] Under the powder preparation parameters of Comparative Example 13, powder preparation was unsuccessful; the molten metal failed to pass through the guide tube diameter of the tundish crucible, resulting in tundish blockage. (See [link to relevant documentation]). Figure 10 As shown.
[0072] This shows that the process parameters for preparing nickel-based alloy powder by atomization in Comparative Example 13 are not suitable.
[0073] Comparative Example 14 The difference from Example 1 is that in step (2): the atomization pressure of the powder preparation in Comparative Example 14 is different from that in Example 1, but the rest is the same.
[0074] Among them, Comparative Example 14 was prepared from powder raw materials: All raw materials were mixed and nickel-based superalloy powder was prepared by argon atomization system. The crucible was a zirconia crucible, the melting power was 60kW, the holding time was 15min, the melting temperature was 1500℃, and the atomization pressure was 3.0MPa. The nickel-based alloy powder with a particle size of 15~53μm was screened out by vibrating sieving equipment for laser additive manufacturing.
[0075] Figure 11 The scanning electron microscope images of nickel-based superalloy powder under the gas atomization process parameters of Comparative Example 14 show that the powder has good sphericity, contains a lot of satellite powder, and the powder particle size distribution meets the raw material requirements of the selective laser melting additive manufacturing process.
[0076] The raw material input and powder output data for this comparative example are shown in Table 7.
[0077] It can be seen that, compared with Example 1, the powder prepared under the process parameters of Comparative Example 14 has poor quality and low yield of 15~53μm powder, indicating that the process parameters for atomization preparation of nickel-based alloy powder in Comparative Example 14 are not suitable.
[0078] Table 7
[0079] Comparative Example 15 The difference from Example 1 is that in step (2): the atomization pressure of the powder prepared in Comparative Example 15 is different from that in Example 1, but the rest is the same.
[0080] Among them, Comparative Example 15 was prepared from powder raw materials: All raw materials were mixed and nickel-based superalloy powder was prepared by argon atomization system. The crucible was a zirconia crucible, the melting power was 60kW, the holding time was 15min, the melting temperature was 1500℃, and the atomization pressure was 5.0MPa. The nickel-based alloy powder with a particle size of 15~53μm was screened out by vibrating sieving equipment for laser additive manufacturing.
[0081] Figure 12 The scanning electron microscope images of nickel-based superalloy powder under the gas atomization process parameters of Comparative Example 15 show that the powder has good sphericity, contains a lot of satellite powder, and the powder particle size distribution meets the raw material requirements of the selective laser melting additive manufacturing process.
[0082] The raw material input and powder output data for this comparative example are shown in Table 8.
[0083] It can be seen that, compared with Example 1, the powder prepared under the process parameters of Comparative Example 15 has poor quality and low yield of 15~53μm powder, indicating that the process parameters for atomization preparation of nickel-based alloy powder in Comparative Example 15 are not suitable.
[0084] Table 8
[0085] Comparative Example 16 The difference from Example 1 is that in step (1): compared with Example 1, the chemical composition of the alloy in Comparative Example 16 is different from that in Example 1, but the rest is the same.
[0086] The chemical composition of the additively manufactured nickel-based superalloy in Comparative Example 16 is as follows: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 4.0 wt.%, Ti: 3.7 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.15 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 1.0wt.%, the balance is Ni.
[0087] Microstructure diagram of the printed part prepared from the 16-component powder in Comparative Example 16, see [link / reference]. Figure 13 As shown. From Figure 13 It can be seen that a large number of cracks appeared inside the sample prepared by the components in Comparative Example 16, indicating a high degree of crack sensitivity.
[0088] This shows that excessive mass fractions of Al and Ti, the γ' phase forming elements, greatly increase the risk of cracking during additive manufacturing of nickel-based alloys.
[0089] In summary, the additive manufacturing method for nickel-based superalloys and their powders provided by this invention effectively solves the cracking problem in additive manufacturing of alloys with high crack sensitivity by precisely controlling the content of trace elements such as C, Zr, and B; by introducing a small amount of Sc element into the alloy composition, the high-temperature ductility of the alloy is improved; and by designing the process parameters for gas atomization powder preparation and the melt viscosity design, the optimal preparation process for additive manufacturing nickel-based superalloy powder raw materials is obtained, providing a systematic solution for high internal quality and one-time integral forming of complex structural parts, which has important theoretical significance and industrial application value.
[0090] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.
Claims
1. A nickel-based superalloy for additive manufacturing, characterized in that: The additive manufacturing nickel-based superalloy raw materials comprise, by weight percentage, Co: 8.0-10.0wt.%, Cr: 15.0-17.0wt.%, Al: 3.2-4.0wt.%, Ti: 3.2-3.7wt.%, Ta: 1.5-3.0wt.%, W: 2.0-4.0wt. %, Mo: 1.5-3.0wt.%, Nb: 0.5-2.0wt.%, C: 0-0.2wt.%, Zr: 0-0.15wt.%, B: 0-0.02wt.%, Sc: 0-1.0wt.%, the balance is Ni; Among them, the strengthening phases in the microstructure of additively manufactured nickel-based superalloys include multi-level γ′ phases and carbides; among them, the multi-level γ′ phases include a first γ′ phase, a second γ′ phase, and a third γ′ phase; The density of additively manufactured nickel-based superalloys is not less than 99.0%, and there are no internal cracks.
2. The additive manufacturing nickel-based superalloy according to claim 1, characterized in that: The additively manufactured high-temperature alloy comprises the following chemical composition by weight percentage: Co: 8.0-9.0 wt.%, Cr: 15.0-16.0 wt.%, Al: 3.5-3.7 wt.%, Ti: 3.4-3.6 wt.%, Ta: 1.5-3.0 wt.%, W: 2.0-3.0 wt.%, Mo: 1.5-2.0 wt.%, Nb: 0.5-2.0 wt.%, C: 0.1-0.15 wt.%, Zr: 0.05-0.10 wt.%, B: 0.005-0.010 wt.%, Sc: 0-1.0 wt.%, with the balance being Ni.
3. The additive manufacturing nickel-based superalloy according to claim 2, characterized in that: The additively manufactured high-temperature alloy comprises the following chemical composition by weight percentage: Co: 9.0 wt.%, Cr: 16.0 wt.%, Al: 3.7 wt.%, Ti: 3.5 wt.%, Ta: 2.0 wt.%, W: 2.5 wt.%, Mo: 1.5 wt.%, Nb: 2.0 wt.%, C: 0.15 wt.%, Zr: 0.1 wt.%, B: 0.01 wt.%, Sc: 1.0 wt.%, with the balance being Ni.
4. The additive manufacturing nickel-based superalloy according to any one of claims 1 to 3, characterized in that: It also has the following characteristics: (i) The tensile strength at room temperature in the printed state exceeds 1200 MPa, and the elongation at break at room temperature exceeds 20%; (ii) The tensile strength at room temperature after aging treatment exceeds 1380 MPa, and the elongation at break exceeds 25%; (iii) The tensile strength at 650℃ after aging treatment exceeds 1200MPa and the elongation at break exceeds 20%.
5. A method for preparing a nickel-based superalloy for additive manufacturing, characterized in that: include The raw materials are weighed and prepared into a mixed powder according to any one of claims 1 to 3 by mass fraction; The above-mentioned mixed powder was placed in an induction melting furnace and vacuum melted; Argon gas is used as a medium to atomize the smelted powder; The prepared powder is sieved, vacuum dried, and then set aside for later use. Nickel-based superalloy powder was subjected to additive manufacturing to obtain a printed nickel-based superalloy. The printed part is subjected to hot isostatic pressing (HIP) treatment to obtain the HIP-treated printed part. The printed part after hot isostatic pressing is subjected to solution treatment and aging treatment to obtain a nickel-based high-temperature alloy after additive manufacturing aging treatment.
6. The method for preparing the nickel-based superalloy for additive manufacturing according to claim 5, characterized in that: The dried and sieved alloy powder has an average particle size of 15~53μm after sieving. The vacuum melting process is carried out at a melting temperature of 1450~1600℃, a gas pressure of 2.2~3.5MPa, and a vacuum degree of 20~70Pa. The atomization powdering is carried out under an argon atmosphere with a purity of 99.99% and an atomization pressure of 3.5~4.5MPa.
7. The method for preparing additively manufactured nickel-based superalloys according to claim 5, characterized in that: Selective laser cladding additive manufacturing (SLM) was used to additively process nickel-based superalloy powder to obtain printed samples. The parameters of SLM were as follows: laser power of 150~250W, scanning rate of 600~1100mm / s, layer rotation angle of 90°, single layer thickness of 0.03~0.05mm, track spacing of 0.06~0.10mm, and laser spot diameter of 0.05~0.08mm. Ar gas was used as the protective gas.
8. The method for preparing additively manufactured nickel-based superalloys according to claim 5, characterized in that: The hot isostatic pressing (HIP) treatment is performed at a temperature of 1150~1200℃ and a pressure of 175~180MPa. The hot isostatic pressing is performed at the temperature and pressure for 2 hours, and then cooled in the furnace to obtain the printed part after HIP treatment. The heating rate of the printed part to the temperature of the hot isostatic pressing is 8~10℃ / min.
9. The method for preparing additively manufactured nickel-based superalloys according to claim 5, characterized in that: The printed part after hot isostatic pressing is heated to 1150~1160℃ and subjected to solution treatment for 1.5~2h. After air cooling, a solution-treated sample is obtained. The solution-treated printed part is then heated to 780~800℃ and subjected to aging treatment for 22~24h. After air cooling, an additively manufactured nickel-based superalloy is obtained. The heating rate is 4.5~5℃ / min.
10. The method for preparing additively manufactured nickel-based superalloys according to claim 5, characterized in that: Before the hot isostatic pressing (HIP) step, a heat treatment design step is also included; wherein, the heat treatment design step further includes: determining the range of HIP and process parameters: based on the structural characteristics of the printed part, selecting the HIP to eliminate internal pores and cracks, and improving the density and mechanical properties of the material; determining the required melting temperature of γ′ and the transformation temperature of the precipitated phase of the additive manufacturing high-temperature alloy, and determining the process parameters of HIP to avoid melt-out; designing the solution and aging treatment regime: designing the process parameters of the solution and aging treatment regime so that the microstructure of the additively manufactured nickel-based high-temperature alloy after aging treatment includes γ′ phases of three sizes.